2021
DOI: 10.1186/s12864-021-07600-7
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and transcriptional characterization of DNA methyltransferases conferring temperature-sensitive male sterility in wheat

Abstract: Background DNA methyltransferase (DMT) genes contribute to plant stress responses and development by de novo establishment and subsequent maintenance of DNA methylation during replication. The photoperiod and/or temperature-sensitive genic male sterile (P/TGMS) lines play an important role in hybrid seed production of wheat. However, only a few studies have reported on the effect of DMT genes on temperature-sensitive male sterility of wheat. Although DMT genes have been investigated in some pla… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 74 publications
(53 reference statements)
1
0
0
Order By: Relevance
“…The quantitative advantage demonstrated that the DME subfamily may experience significant expansion during three WGD events, and the autotetraploid speciated in the most recent WGD (~ 11.2–10.5 Mya) [ 17 ]. In this study, we found that CpC5-MTase and CpdMTase genes were mostly involved in WGD and segmental replication (Table S 1 ), which is consistent with the expansion of C5-MTase gene family in autopolyploid sugarcane ( Saccharum spontaneum ) and allopolyploid wheat ( Triticum aestivum ) [ 33 , 36 ]. Segmented replication often occurs in plants, which experienced polyploidy events resulting in a large number of chromosome blocks in the genome.…”
Section: Discussionsupporting
confidence: 79%
“…The quantitative advantage demonstrated that the DME subfamily may experience significant expansion during three WGD events, and the autotetraploid speciated in the most recent WGD (~ 11.2–10.5 Mya) [ 17 ]. In this study, we found that CpC5-MTase and CpdMTase genes were mostly involved in WGD and segmental replication (Table S 1 ), which is consistent with the expansion of C5-MTase gene family in autopolyploid sugarcane ( Saccharum spontaneum ) and allopolyploid wheat ( Triticum aestivum ) [ 33 , 36 ]. Segmented replication often occurs in plants, which experienced polyploidy events resulting in a large number of chromosome blocks in the genome.…”
Section: Discussionsupporting
confidence: 79%